How do Indian mothers use feeding practices with children?. Issue 4 (19th December 2016) - Vohra, Jyoti; Soni, Pavleen
Abstract : Purpose: The undesirable effects of TV advertisements and general parenting responsibility propel mothers to monitor and control the eating habits of children through meal time actions and feeding practices. The purpose of this paper is to identify feeding practices used by Indian mothers through the Comprehensive Feeding Practices Questionnaire (CFPQ) developed by Musher-Eizenman and Holub (2007) and to investigate differences in the use of feeding practices across demographic variables. Design/methodology/approach: Using a cross-sectional design, a structured and pre-tested questionnaire was used to collect data from 473 mothers of children aged four to 11 years from Punjab (India). Data were analysed using exploratory factor analysis, confirmatory factor analysis (CFA) and ANOVA. Findings: The present study confirms the validity and reliability of the nine-factor model through CFA with 28 items in the Indian context than original CFPQ. Further, significant differences exist in the responses of mothers for feeding practices followed with children across age and gender of child, mother's education status and monthly family income. Practical implications: Parents may understand the nature of feeding practices to mediate unhealthy food consumption habits of children. The government should formulate codes or regulations to sufficiently monitor food marketing activities directed at children. The food marketing companies should also act responsibly to protect well-being of children. Originality/value: This piece of research is important as no such study (to the best of researchers' knowledge) has already been conducted in India even though dietary patterns of children are transforming tremendously.